Repair of gluteus medius tears with bioinductive collagen patch augmentation: initial evaluation of safety and imaging. Issue 3 (2nd July 2022) - Day, Molly A; Hancock, Kyle J; Selley, Ryan S; Swartwout, Erica L; Dooley, Matthew; Shamrock, Alan G; Nwachukwu, Benedict U; Greditzer, Harry G; Ranawat, Anil S
ABSTRACT: The purpose of this study was to perform an initial, prospective evaluation of imaging findings and outcomes after open surgical repair of gluteus medius tendon tears with bioinductive collagen patch augmentation. A prospective study was performed of patients with clinical and magnetic resonance imaging (MRI) evidence of symptomatic gluteus medius tears who underwent open, double-row suture anchor repair with bioinductive bovine collagen patch augmentation. Preoperative and 6-month postoperative MRIs were reviewed by a fellowship-trained musculoskeletal radiologist, and outcome scores were recorded preoperatively and 6 months postoperatively [Hip Outcome Score (HOS) Sport; HOS Activities of Daily Living (HOS ADL); Modified Harris Hip Score (mHHS) and International Hip Outcomes Tool (iHOT-33)]. Nine patients, four high-grade tears (≥50% tendon thickness) and five low-grade tears (<50% thickness) underwent surgical repair. At 6 months, 7/9 (77.8%) of tendons were qualitatively classified as completely healed on MRI, with no complications. Mean tendon thickness increased significantly: mediolateral dimension by 5.8 mm ( P < 0.001), anteroposterior dimension by 4.1 mm ( P = 0.02) and cross-sectional area (CSA) by 48.4 mm 2 ( P = 0.001). Gluteus medius and minimus CSA did not change significantly ( P > 0.05). Patients demonstrated improvements in mean scores for HOS ADL, mHHS and iHOT that met defined minimum clinically important differences ( P < 0.05). Open surgical repair of gluteus medius tendon tears with bioinductive collagen patch augmentation is safe and associated with increased tendon thickness on postoperative MRI. Early outcome scores are encouraging and should be evaluated after patients have completed postoperative rehabilitation to measure the whole effect of treatment.